2020
DOI: 10.18632/aging.102738
|View full text |Cite
|
Sign up to set email alerts
|

Late-life obesity is a protective factor for prodromal Alzheimer’s disease: a longitudinal study

Abstract: Higher body mass index (BMI) in late-life has recently been considered as a possible protective factor for Alzheimer's disease (AD), which yet remains conflicting. To test this hypothesis, we have evaluated the crosssectional and longitudinal associations of BMI categories with CSF biomarkers, brain β-amyloid (Aβ) load, brain structure, and cognition and have assessed the effect of late-life BMI on AD risk in a large sample (n = 1,212) of nondemented elderly from the Alzheimer's Disease Neuroimaging Initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 42 publications
10
34
0
Order By: Relevance
“…Consistent evidences have proposed a higher risk of developing AD among middle-aged patients with raised body mass index (BMI) whereas overweight or obesity in late-life might have protective effects on cognition (46,47). Particularly the HR for AD was 0.89 (95% CI 0.81-0.98) among those with high late-life BMI, in contrast, there was 20% increased risk for AD (95% CI 1.09-1.33) among those with greater loss of BMI from midlife to late-life (46).…”
Section: Obesitymentioning
confidence: 99%
“…Consistent evidences have proposed a higher risk of developing AD among middle-aged patients with raised body mass index (BMI) whereas overweight or obesity in late-life might have protective effects on cognition (46,47). Particularly the HR for AD was 0.89 (95% CI 0.81-0.98) among those with high late-life BMI, in contrast, there was 20% increased risk for AD (95% CI 1.09-1.33) among those with greater loss of BMI from midlife to late-life (46).…”
Section: Obesitymentioning
confidence: 99%
“…During the last years, studies incorporating AD biomarkers have shown that higher baseline levels of amyloid-β (Aβ) deposition, as measured by positron emission tomography (PET), and higher cerebrospinal fluid (CSF) levels of tau/Aβ42 ratio are associated with greater prospective body weight decline [ 15 , 16 ], and a recent study has reported a negative correlation between BMI change and amyloid-PET burden [ 17 ]. Other studies have found a negative correlation between BMI and Aβ and tau deposition in the brain of cognitively unimpaired elders [ 18 21 ]. While these studies have focused on associations with continuous measures of AD biomarkers, few studies have evaluated whether weight loss predicts AD biomarker positivity using categorical outcomes, such as amyloid-PET visual read results.…”
Section: Introductionmentioning
confidence: 98%
“…Obesity is considered a risk factor for AD [ 1 , 2 , 3 ]. However, the relationship between body weight and dementia appears complex [ 4 , 5 , 6 ], and recent observations even pose a protective role of late-life excess weight in AD [ 7 ]. Taking into account the worrying worldwide prevalence of obesity and dementia [ 8 , 9 ], greater knowledge of possible links between the two conditions is imperative.…”
Section: Introductionmentioning
confidence: 99%